The Effect Of Giving Trichoderma Sp And Fertilizer Fertilizer On Redeed Production And Production (Amaranthus Amoena Voss) - A. Miftakhurrohmat; Ella Nur Fauzyah (Nabatia, 2018)
Red spinach plant originally known as vegetable crop, Trichoderma sp function provides auksin signals and can also accelerate the growth of plants, especially vegetable crops. Giving fertilizer N, P and K is an effort to increase crop production. Manure can indeed increase the availability of nutrients for plants, research aims to determine the effect of giving Trichoderma sp and type of fertilizer on the growth and production of red spinach plants implemented in the Village Sidokepung Buduran Sidoarjo District Start July-August 2017. Factorial research using Randomized Block Design (RAK) with two factors and repeated three times The first factor is Trichoderma sp (T) consists of 4 kinds: T1 = Trichoderma sp, T2 = Trichoderma sp-Jjr-02, T3 = Trichoderma sp -Jtr-01, T4 = Trichoderma sp-Pjn-01. The second factor is the type of fertilizer (P) which consists of 3 kinds: P0 = tampa fertilizer, P1 = kima fertilizer, P2 = manure. Fariabel observed were Plant Height, Leaf Amount, Stem diameter, Wet Weight Plant, Dry Plant Weight ,. The results showed the interaction of treatment of Trichoderma sp and type of fertilizer to plant height of 14 HST, 21HST, 28HST and on the number of leaves showed interaction at 14HST, 28HST and interaction on wet weight of plant. In the type of fertilizer treatment occurs interaction in almost all observations of plant height, number of leaves, diameterbatang, wet weight and dry weight of plants.